Effect of γ-irradiation in combination with natural antimicrobial formulation on microbial inactivation, protein digestibility and quality of mothers' milk. (August 2022) - Balaji, Athishparsuram Serukaluthur; Allahdad, Zahra; Lacroix, Monique
Abstract: The combined effect of γ-irradiation (5 kGy) and four antimicrobial formulations developed for their antimicrobial properties (1, Oregano/Mediterranean formulation/Citrus extract/Lactic acid; 2, Cinnamon/Lemongrass/Citrus extract/Citric acid; 3, Oregano/Mediterranean formulation/Citrus extract/Citric acid); 4, Cinnamon/Lemongrass/Citrus extract/Lactic acid) was investigated in terms of microbial inactivation of selected foodborne pathogens, lactose and immunoglobulin composition, in vitro protein digestibility, peptide profile, physicochemical properties of mothers' milk in frozen condition. γ-Irradiation treatment along with formulation 3 and 4 eliminated all tested pathogens including sporulated Bacillus cereus that was resistant to γ-irradiation in the presence of formulation 1 and 2. Furthermore, combined treatment did not significantly alter the lactose, immunoglobulins and lipid oxidation of mothers' milk. Protein digestibility increased in the irradiated milk and hydrolysis of larger proteins to smaller peptides was demonstrated. Irradiated samples had a minimal change in colour and viscosity. Hence, combined treatment was effective in preservation of the quality of frozen mothers' milk.